Environmentalism, Libertarianism, and Privat Property Rights - Block, Walter E. Block (University of Darussalam Gontor Press, 2024)
In the view of most commentators, academic and otherwise, “free market environmentalism” is a veritable contradiction in terms. It is widely thought that to the extent that one favors protecting the environment, or, even, studying it, to that extent one must reject free enterprise and private property rights. The only scholars who wish to save the fauna and flora, ensure that we do not trash the planet, must eschew such right-wing considerations and pretty much embrace the polar opposite viewpoint. In the extreme, free market environmentalism is not only a logical contradiction, it reeks of fascism, profiteering, and destruction of this our third rock from the sun. Shahar does not at all fit this bill. Although a critic of free enterprise environmentalism, he treats this viewpoint sympathetically. He does not give it the back of his hand in derision. You will look in vain for contempt in his rejection of this philosophy. Rather, his critique is a careful, cautious, knowledgeable treatment of this perspective. All the more reason that his criticisms be examined critically, since in my view, the best last chance of saving the environment lies in exactly the direction opposite to the one he avers.